Comparative molecular study of Enterococcus faecalis in endodontic treatment pre and postdiode laser application - Israa Hadi Hashim; Fatima Abood Malik; Ahmed Ghanim Mahdi (Medical Journal of Babylon)
Abstract Background: Endodontic infections are polymicrobial, with the majority of bacteria being anaerobic and others being facultative. Objective: To detect and measure the level of Enterococcus faecalis in infected root canals during traditional cleaning techniques and after diode laser application by using real-time polymerase chain reaction (RT-PCR). Materials and Methods: Ninety samples were collected from 30 participant patients complaining of acute or chronic pulpitis with an age range of 18–50 years old; the teeth indicated endodontic treatment, including both anterior and posterior teeth. Thirty swabs were taken preinstrumentation, and then 30 swabs were taken after instrumentation and canal irrigation using sodium hypochlorite 5.25%, and then 30 swabs were taken in the same manner after the root canal sterilization with the diode laser. Results: This study included 30 patients with root canal infection presented with a mean age of 31.7 ± 8.6 years and a range of 18–50 years; Female patients were more than males (34.3% vs. 36.7%). The mean E. faecalis copy number was significantly reduced from precleaning status to postcleaning with sodium hypochlorite (5.25%) and postlaser therapy (P = 0.05). Conclusions: RT-PCR assay is a highly effective, dependable, and rapid technique for accurate detection and copy number counting of E. faecalis in the infected root canal; this molecular and clinical study supports the diode laser application of 940-nm WL as an adjuvant tool combined with sodium hypochlorite (5.25%) in canal disinfection during root canal treatment to reduce E. faecalis copy numbers.